The Relationship Between Students Interest in Learning and Their Achievement in Islamic Cultural History - Vadila, Fara; Yanti, Hernina; Nazaruddin, Nazaruddin; Abdi, Hamdani; Khoiriyati, Wildatun Rizka; Asrida, Asrida (Suluah Pasaman, 2023)
Education plays a role in shaping individuals. In Islamic religious education, the Islamic Cultural History subject has an important role in forming students' religious character and skills. Student interest in learning is a key factor in increasing the effectiveness of learning Islamic Cultural History. This research aims to explore the relationship between students' interest in learning and learning outcomes in the History of Islamic Culture at Madrasah Tsanawiyah. Through in-depth analysis, this research will reveal the extent to which students' interest in learning can influence their achievement of learning outcomes in the Islamic Cultural History subject. From the results of research conducted by the author at the Madrasah Tsanawiyah, it can be concluded that class VIII students' interest in learning at the Madrasah Tsanawiyah, class VIII students at the Madrasah Tsanawiyah are in the medium category with a percentage of (61%). Second, is there a relationship between interest in learning and student learning outcomes in the History of Islamic Culture class VIII subject at Madrasah Tsanawiyah. The result is that there is a very significant relationship between interest in learning and the learning outcomes of Islamic Cultural History students at Madrasah Tsanawiyah, namely 0.213 with a percentage of 21.3% while the remaining 78.7% is caused by other factors.